Comparison of the pharmacokinetics of tilmicosin in plasma and lung tissue in healthy chickens and chickens experimentally infected with Mycoplasma gallisepticum. Issue 4 (4th March 2020) - Zhang, Nan; Liu, Zhenxian; Wei, Yanzhe; Zhang, Chuanzhen; Mao, Chunxiao; Cai, Qinren; Shen, Xiangguang; Ding, Huanzhong
Abstract: The objectives of this study were to compare the plasma and lung tissue pharmacokinetics of tilmicosin in healthy and Mycoplasma gallisepticum ‐infected chickens . Tilmicosin was orally administered at 4, 7.5 and 10 mg/kg body weight (b.w) for the infected and 7.5 mg/kg b.w for the uninfected control group. We found no significant differences in plasma tilmicosin pharmacokinetics between diseased and healthy control chickens. In contrast, the lung tissues in M. gallisepticum ‐infected chickens displayed a t 1/2 (elimination half‐life) 1.76 times longer than for healthy chickens. The C max (the maximum concentration of drug in samples) of tilmicosin in M. gallisepticum ‐infected chickens was lower than for controls at 7.5 mg/kg b.w ( p  < .05), and the AUCinf (the area under the concentration–time curve from time 0 extrapolated to infinity) in infected chickens was higher than for the healthy chickens ( p  < .05). The mean residence time of tilmicosin in infected chickens was also higher than the healthy chickens. These results indicated that the lungs of healthy chickens had greater absorption of tilmicosin than the infected chickens, and the rate of elimination of tilmicosin from infected lungs was slower.